Synergistic Activity Of Ceftriaxone And Polyalthia Longifolia Leaves Extract Against Methicillin Resistant Staphylococcus Aureus (Mrsa) - Valiappan, Ranjutha (2021)
Methicillin‐resistant Staphylococcus aureus (MRSA) infection has become one of the most significant pathogenic bacterial infection health issues in developing countries. Furthermore, the most important mecA gene that is encodes a novel penicillin-binding protein PBP2a contributes to the methicillin resistance in MRSA strains. Therefore, new alternative strategies are needed to address this issue by developing a new antimicrobial agent, modifying the existing antibiotic activity with a combination of plant extracts as resistance modifying agents, or using the plant extract combined with existing antibiotics against resistant bacteria. Consequently, the current study was conducted to evaluate the antibiotic modifying activity and synergistic effects of methanol extract Polyalthia longifolia (Sonn.) Thwaites (Annonaceae family) against MRSA in combination with ceftriaxone. The antibiotic modifying activity and synergistic effects of P. longifolia leaf methanol extract (PLLME) were evaluated in this study by disc diffusion method, broth microdilution method, checkerboard microdilution method, and detection of the mecA gene suppression by multiplex Polymerase chain reaction (PCR).